Trigeminal Cardiac Reflex and Cerebral Blood Flow Regulation - Lapi, Dominga; Scuri, Rossana; Colantuoni, Antonio (Frontiers in Neuroscience, 2016)
The stimulation of some facial regions is known to trigger the trigemino-cardiac reflex: the main stimulus is represented by the contact of the face with water. This phenomenon called diving reflex induces a set of reactions in the cardiovascular and respiratory systems occurring in all mammals, especially marine (whales, seals). During the immersion of the face in the water, the main responses are aimed at reducing the oxygen consumption of the organism. Accordingly reduction in heart rate, peripheral vasoconstriction, blood pooling in certain organs, especially the heart and brain, and an increase in blood pressure have been reported. Moreover, the speed and intensity of the reflex is inversely proportional to the temperature of the water: more cold the water, more reactions as described are strong. In the case of deep diving an additional effect, such as blood deviation, has been reported: the blood is requested within the lungs, to compensate for the increase in the external pressure, preventing them from collapsing. The trigeminal-cardiac reflex is not just confined to the diving reflex; recently it has been shown that a brief proprioceptive stimulation (10 min) by jaw extension in rats produces interesting effects both at systemic and cerebral level, reducing the arterial blood pressure and vasodilating the pial arterioles. The arteriolar dilation is associated with rhythmic diameter changes characterized by an increase in the endothelial activity. Fascinating the stimulation of trigeminal nerve is able to activated the nitric oxide release by vascular endothelial. Therefore the aim of this review was to highlight the effects due to trigeminal cardiac reflex induced by a simple mandibular extension, because produced opposite effects compared to those elicited by the diving reflex as it induces hypotension and modulation of cerebral arteriolar tone.